Nonalcoholic Steatohepatitis is the Most Rapidly Increasing Indication for Liver Transplantation in Young Adults in the United States. Issue 4 (April 2018) - Doycheva, Iliana; Issa, Danny; Watt, Kymberly D.; Lopez, Rocio; Rifai, Ghassoub; Alkhouri, Naim
Abstract : Goals: To analyze the frequency and trend of liver transplantation (LT) for nonalcoholic steatohepatitis (NASH) cirrhosis in young adults aged 18 to 40 years and to assess post-LT outcomes in this age group. Background: NASH is currently the fastest-growing indication for LT in US adults. It is believed that NASH is a rare indication for LT among young adults. Study: Using the United Network for Organ Sharing database, we performed a retrospective cohort analysis of all LTs in young adults between 2002 and 2012. Incidence rate ratio was calculated for each indication. Results: A total of 5157 young adults underwent LT over the study period—54% were male, 23% obese. Mean (±SD) age and body mass index were 31.6±6.7 years and 26.3±6.1 kg/m 2, respectively. The incidence of LTs performed for NASH cirrhosis increased from 0.53% in 2002 to 4.46% in 2012. NASH was the most rapidly growing indication for LT among all other etiologies with a 14% increment per year (incidence rate ratio, 1.14; 95% confidence interval, 1.09-1.20, P <0.001). The 5-year post-LT outcomes were comparable between NASH and non-NASH recipients, but graft survival was lower and retransplantation cumulative rates were higher in NASH recipients compared with those with other metabolic liver diseases (63.5% vs. 81.4%, P =0.003 and 12.7% vs. 4.2%, P =0.046, respectively). Conclusions: NASH is the fastest-growing indication for LT among young US adults aged 18 to 40 years and now accounts for almost 5% of all LTs in this age group. Abstract : Supplemental Digital Content is available in the text.